Numerical solution of the problem of propagation of forced electroelasticity waves in a solid piezoceramic cylinde - Grigorenko, A.Ya.; Loza І.А.; Sperkach S.О.; Bezuglaya А.D. (Reports of the National Academy of Sciences of Ukraine, 2022)
The propagation of forced axisymmetric waves in a solid homogeneous and inhomogeneous piezoceramic cylinder with axial polarization based on the linear theory of elasticity and the linear electromechanical coupling is investigated. A mechanical load to the lateral surface of the cylinder is applied and it is free of the electrodes. The case of the continuously inhomogeneous piezoceramic cylinder material is considered. The boundary conditions at singular point of a solid piezoceramic cylinder are formulated. The discretely continual analytical numerically approach to solve of the problems of the forced wave propagation in the piezoceramic solid cylindrical bodies is proposed. The three-dimensional problem of the theory of electroelasticity in the partial derivatives (by presenting components of the elasticity tensor, component of displacement vectors, electrical induction and electrostatic potential by running waves in the axial direction) is reduced to the boundary value problems for the system of the ordinary differential equations. The оne-dimensional problem is solved by a stable method of discrete orthogonalization. The kinematic analysis of the propagation of forced electroelastic waves in a solid piezoceramic homogeneous and inhomogeneous cylinder is carried out